Pengawasan Hukum terhadap Peredaran Rokok Ilegal oleh Kantor Pengawasan dan Pelayanan, Bea dan Cukai Tipe Madya Pabean C Cirebon - Jeshline Efellien Wirawan; Irma Maulida (Jurnal Hukum Lex Generalis, 2026)
The circulation of illegal cigarettes continues to threaten state revenue from the excise sector, necessitating effective supervision by Customs and Excise. This study aims to analyze the form of supervision of the circulation of illegal cigarettes by the Cirebon Type C Customs and Excise Supervision and Service Office and the obstacles in its implementation. The method used is empirical juridical through a statutory regulatory approach and interviews. The results of the study indicate that supervision is carried out in a repressive, preventive and collaborative manner. Throughout 2025, 31,217,302 illegal cigarettes were successfully secured with the potential to save Rp23,288,107,292 in Tobacco Product Excise. Supervision needs to be strengthened through increased personnel, intelligence-based supervision and inter-agency synergy.